Applying communication theory for professional life : - Dainton, Marianne (SAGE Publications, Inc, 2015)
Introduction to communication theory -- Theory development -- Cognition and intrapersonal communication -- Individual and social approaches to communication -- Interpersonal communication -- Culture -- Persuasion -- Group communication -- Organizational communication -- Mediated communication -- Mass communication -- What should a communicator do?